Migrations and Borders: Practices and Politics of Inclusion and Exclusion in Europe from the Nineteenth to the Twenty-first Century. Issue 4 (8th August 2019) - Fauser, Margit; Friedrichs, Anne; Harders, Levke
ABSTRACT: Current media images of a "fortress Europe" suggest that migrations and borders are closely connected. This special issue brings together scholars from history, sociology and anthropology to explore cross-border mobility and migration during the formation, development, and transformation of the modern (nation-)state explicating the conflictive and fluctuating character of borders. The historical perspective demonstrates that such bordering processes are not new. However, they have developed new dynamics in different historical phases, from the formation of the modern (nation-)state in the nineteenth century to the creation of the European Union during the second half of the twentieth. This introduction explains the dynamic relationships between borders and migratory movements in Europe from the nineteenth century to the present by approaching them from four different, overlapping angles, which the articles analyze in more detail: (1) the multiple actors involved, (2) scales and places of borders and their crossings, (3) the instruments and techniques employed, and (4) the significance of social categories. Focusing on the historical, local specificity of the complex relations between migration and boundaries will help denaturalize the concept of the border as well as further reflection on the shifting definitions of migration and belonging.